The nature of the Japanese state : rationality and rituality - McVeigh, Brian J. (Nissan Institute/Routledge Japanese studies series., 1998)
In this adventurous new study the author demonstrates how conflicting impressions of Japan can be reconciled and a greater understanding of the state achieved. Engagement with debates over bureaucracy's role in Japanese politics is included.